Multilingual education for social justice : globalising the local - International Conference on Multilingual Education: Challenges, Perspectives, and Opportunities (2008 : Zakir Husain Centre for Educational Studies); Mohanty, Ajit K.; UNICEF (New Delhi : Orient Blackswan, 2009)
Contributed papers presented at the International Conference on Multilingual Education: Challenges, Perspectives, and Opportunities, held at the Zakir Husain Centre for Educational Studies, Jawaharlal Nehru University, New Delhi in February 2008, organized by UNICEF and others.
Includes bibliographical references p. 343-385 and index.
Keywords: Multicultural education -- Congresses; Language and education -- Congresses; Multilingualism -- Social aspects -- Congresses